HIDROCARBONETOS EM ÁGUA DO MAR: RESULTADOS DO MONITORAMENTO EM ÁREA DE PRODUÇÃO DE PETRÓLEO NA BACIA DO CEARÁ - Wagener, Angela L.R.; Carreira, Renato S.; Hamacher, Cláudia; Scofield, Arthur L. (Geochimica Brasiliensis, 2012)